THE LEGAL SIGNIFICANCE OF COMBATING THE FINANCING OF EXTREMISM (American Journal of Interdisciplinary Research and Development, 2023)
This article focuses on the cases where the politicization of the religious factor causes financial freedom in the activities of a number of informal streams and directions. Currently, there is an opinion about putting an end to this activity, holding the financing of the extremist activities to account on a legal basis.